Analysis of Economic Growth Determinants in China - Rofiqoh, Siti (Universitas Negeri Semarang, 2022)
This study aims to analyze the determinants of economic growth in China for the period 1980-2020. The benefits of this research are expected to be input for the Chinese government. The data used are time-series data from 1980-to 2020. The analytical tool used is multiple regression with the Ordinary Least Square (OLS) method. The results show that the unemployment rate has a negative and significant effect on China's economic growth, the contribution of industry and the level of exports has a positive and significant impact on China's economic growth. Meanwhile, inflation has a negative and insignificant effect on China's economic growth in 1980-2020. As well as the joint influence of the variable unemployment rate, industry contribution, export rate and inflation on economic growth. The determinant coefficient of 83.8% can be explained by the independent variable on the dependent variable, and the rest is explained by other variables outside the model studied. Penelitian ini bertujuan untuk menganalisis determinan pertumbuhan ekonomi di Negara China periode 1980-2020. Manfaat penelitian ini diharapkan menjadi bahan masukan pemerintah Negara China. Data yang digunakan berupa data time series dari tahun 1980-2020. Alat analisis yang digunakan adalah regresi berganda dengan metode Ordinary Least Square (OLS). Hasil penelitian menunjukkan bahwa tingkat pengangguran memiliki pengaruh negatif dan signifikan terhadap pertumbuhan ekonomi China, kontribusi industri dan tingkat ekspor memiliki pengaruh positif dan signifikan terhadap pertumbuhan ekonomi China. Sedangkan untuk inflasi memiliki pengaruh negatif dan tidak signifikan terhadap pertumbuhan ekonomi China tahun 1980-2020. Serta adanya pengaruh secara bersama-sama variabel tingkat pengangguran, kontribusi industri, tingkat ekspor dan inflasi terhadap pertumbuhan ekonomi. Koefisien determinan 83,8% dapat dijelaskan oleh variabel independen terhadap variabel dependen, dan sisanya dijelaskan oleh variabel lain diluar model yang diteliti.